Identifying research particiaption effects through qualitative methods: Feedback from Research Engagement Consultants involved in a pediatric mental health comparative effectiveness trial - Elisabeth A. Stelson; Mallory Bolenbaugh; Briana Woods-Jaeger; Cassidy Branch; Marizen Ramirez (Elsevier, 2021)
Research participation effects (RPEs)-effects due to study design rather than study intervention-have long been acknowledged as a research phenomenon. Identifying RPEs is crucial to understanding the true effects of an intervention and outcomes may change during dissemination. Few researchers systematically identify the potential role of RPEs on their research findings, despite recent calls to capture these effects. This study demonstrates the utility of using qualitative methodologies to detect RPEs in a clinical trial. Research Engagement Consultants (RECs) were parents and children (N=19) who participated in a post-injury mental health trial in three Midwestern states. RECs were hired as part of the research team upon completion of their study participation. RECs participated in two semi-structured interviews detailing their experience in the study and their recovery process. Inter-coder reliability calculations were used iteratively to ensure coding consistency. Thematic analysis indicates that in addition to benefiting from the interventions being tested, RECs additionally reported benefitting from the study design in two primary ways: 1) contact with the research team provided social support; and 2) completion of specific data collection activities facilitated parent-child communication. Analysis of these interviews illustrates how embedding a qualitative evaluation process into clinical trials can help identify unintended RPEs and understand the potential effects of participating in the research process. Additionally, analysis of the qualitative data provides a quality improvement feedback loop to contextualize the results of the study; how the clinical trial environment may influence dissemination effectiveness; and how future research processes could potentially be strengthened. Trial registration number: NCT02323204. Trial registry: clinicaltrials.gov (US National Institutes of Health)